INTRODUCTION TO THE SPECIAL ISSUE: THE LEFT-WING PARTIES IN CENTRAL AND EASTERN EUROPE, TRAJECTORY OF A DECLINE FROM THE POST-COMMUNIST TRANSITION (Studia Politica. Romanian Political Science Review, 2025)
This article reviews the electoral results of left-wing parties in Central and Eastern Europe since 1991 and the fall of Communism. By following the trajectories of left-wing parties, we can identify a three-phase periodization leading to the decline of left-wing parties. First, the reform of the heirs to communism, who converted to Western social democracy and reformed their political élite. This period is characterized by electoral success and government participation for the heirs of communism who have become social democrats. Then came the accession negotiations with the European Union, which brought the European issue to the forefront of the region’s agenda. The social-democratic parties held the issue, giving themselves an image of modernizers with the promise of social and economic progress. This period was marked by even greater electoral success, demonstrating the strength of these parties. Finally, the decline which followed the disillusionment of EU membership after 2008: social-democratic parties have lost their status as modernizers and are no longer able to regain a foothold in society, to the benefit of radical right-wing parties. Thisperiodization leads us to consider the state of the left in the region today, and its reconstruction.